Growth hormone deficiency in megalencephaly‐capillary malformation syndrome: An association with activating mutations in PIK3CA. Issue 1 (15th November 2019) - Davis, Shanlee; Ware, Meredith A.; Zeiger, Jordan; Deardorff, Matthew A.; Grand, Katheryn; Grimberg, Adda; Hsu, Stephanie; Kelsey, Megan; Majidi, Shideh; Matthew, Revi P.; Napier, Melanie; Nokoff, Natalie; et al.
Abstract: Megalencephaly‐capillary malformation syndrome (MCAP) is a brain overgrowth disorder characterized by cortical malformations (specifically polymicrogyria), vascular anomalies, and segmental overgrowth secondary to somatic activating mutations in the PI3K‐AKT–MTOR pathway ( PIK3CA ). Cases of growth failure and hypoglycemia have been reported in patients with MCAP, raising the suspicion for unappreciated growth hormone (GH) deficiency. Here we report an observational multicenter study of children with MCAP and GH deficiency. Eleven participants were confirmed to have GH deficiency, all with very low or undetectable circulating concentrations of insulin‐like growth factor‐1 and insulin‐like growth factor binding protein‐3. Seven underwent GH stimulation testing and all had insufficient responses with a median GH peak of 3.7 ng/ml (range 1.1–8.6). Growth patterns revealed a drastic decline in length z‐scores within the first year of life but then stabilized afterward. Five were treated with GH; one discontinued due to inconsolability. The other four participants continued on GH with improvement in linear growth velocity. Other endocrinopathies were identified in 7 of the 11 participants in this cohort. This study indicates that GH deficiency is associated with MCAP and that children with MCAP and hypoglycemia and/or postnatal growth failure should be evaluated for GH deficiency and other endocrinopathies.